Abrindo a caixa de pandora: uma avaliação das estratégias do enfrentamento à violência contra as mulheres em Maracanaú-CE. - Azevedo, Lidiany Alexandre (2018)
The objective of this study is to evaluate strategies to combat violence against women that are developed in the municipality of Maracanaú / CE. The investigative trails that we constructed were based on an experiential paradigm of public policy evaluation, based on the precepts of the qualitative approach and with an approximation of reality oriented in the ethnographic method. We made use of documentary research, observation, field journaling and comprehensive interviews. We realize that local experience, despite not following all the guidelines proposed by the text of the National Policy on Combating Violence against Women, has been able to confront violence against women with a view to integrating the four axes that comprise it (prevention, combat, assistance and guarantee of rights). This scope is due mainly to the understanding of the subjects of this type of violence as a social problem, due to the inequalities between the genders, as well as to their position of militancy in the defense and guarantee of women's rights. This reality coexists with the lack of direct municipal government investment in gender policies, the lack of a coordination that unifies the action, planning and evaluating the service delivery structure, the lack of constant communication between the services and the consequent lack of information from professionals and users, and the imprecision of statistical data. However, we identify that the institutional actors, through the difficulties encountered, develop strategies for the execution of activities in the services, in the internal and external spaces, and in the social networks that they form with the intention of reaching the conception and execution of the confrontation, walking with potential for the formation of networks of care and to combat violence against women.